Plant-Parasitic Nematodes Associated with Asian Vegetables in Florida - Hung X. Bui; Johan A. Desaeger (EDIS)
Root-knot nematodes (Meloidogyne spp.) are one of the main soilborne pathogens in Florida and cause considerable damage to many vegetables. Asian vegetables are important specialty crops in Florida, but no information is available on their hosts status to plant-parasitic nematodes, in particular to Meloidogyne spp. Therefore, we conducted a survey to learn what Asian vegetables are grown in Florida and plant-parasitic nematodes associated with these crops, and the potential damage these nematodes cause to Asian vegetables.